An adaptive bilateral impedance control based on nonlinear disturbance observer for different flexible targets grasping. (October 2022) - Zhong, Yichen; Wang, Ting; Pu, Yanfeng; Moreno, Ramón
Abstract: The uncertainty of environmental parameters and time-varied characteristics usually generate contact force errors resulting the inaccuracy or even task failed in many tele-operation systems. In order to solve the problem, a novel composite bilateral tele-operation controller is proposed in this paper combining adaptive impedance control with nonlinear disturbance observer-based sliding mode controller. An adaptive impedance controller is constructed to achieve high-precision tracking of desired contact forces and ensure the safety of grasping various flexible targets. A sliding mode controller on the basis of a nonlinear disturbance observer is designed, so as to accurately estimate the composite disturbance signals as well as to ensure the stability and the high accuracy of the trajectory tracking. The stability of the system is proved by the Lyapunov function. Numerical simulations and real robot experiments are performed. Results shows that our method can greatly enhance the safety of the flexible target in the process, minimize the influence of disturbance signals on the system, and improve the robustness of the system. Highlights: An adaptive bilateral impedance control method is proposed. A nonlinear disturbance observer is introduced into the novel bilateral impedance control methods. Numerical simulations and real robot experiments verify the effectiveness of the proposed method.